2020
DOI: 10.1016/j.celrep.2020.108294
|View full text |Cite|
|
Sign up to set email alerts
|

Structural and Functional Insights into an Archaeal Lipid Synthase

Abstract: Highlights d Identification of DGGGP synthase as a member of the UbiA superfamily d Structures determination of Apo-and lipid bound states of DGGGPase d Functional and structural insights into lipid modifying enzyme in three kingdoms d Archaeal lipid biosynthesis, remodeling, and membrane adaptation in cell membrane

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…Opsin, a known scramblase, but not digeranylgeranylglyceryl phosphate synthase (DGGGPase), a lipid-modifying enzyme with nine transmembrane helices, reduced NBD fluorescence by >50% upon addition of dithionite ( Fig. S3 C ; Menon et al, 2011 ; Ren et al, 2020 ). The presence of TMEM41B or VMP1 in liposomes also decreased NBD fluorescence by >50% ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Opsin, a known scramblase, but not digeranylgeranylglyceryl phosphate synthase (DGGGPase), a lipid-modifying enzyme with nine transmembrane helices, reduced NBD fluorescence by >50% upon addition of dithionite ( Fig. S3 C ; Menon et al, 2011 ; Ren et al, 2020 ). The presence of TMEM41B or VMP1 in liposomes also decreased NBD fluorescence by >50% ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The peak fractions were flash frozen in liquid N 2 and stored at −80°C for further experiments. The full-length human opsin (UniProt ID: P03999 ) and DGGPase (UniProt ID: Q57727 ) were purified according to previous reports ( Menon et al, 2011 ; Ren et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The predicted interaction between COA8 and COX10 suggests that COA8 could be a subunit of the heme farnesyltransferase complex. The AlphFold2 model of the COA8-COX10 complex revealed that COA8 forms two long α-helices, and COX10 is a multi-pass transmembrane protein with 9 transmembrane segments, consistent with its homology to proteins in the UbiA prenyltransferase family (Pfam: UbiA) [106, 107] (Figure 5D). The predicted interface residues are mainly mapped to the middle of the second α-helix in COA8 and in between the second and third transmembrane segments of COX10 (Figure 5D), which is part of the cap domains (colored in blue in Figure 5D) previously defined as the connections between transmembrane helices near the active site [107].…”
Section: Resultsmentioning
confidence: 65%
“…Even the highly acid-sensitive geranylgeranyl substituted glycidol was a versatile substrate (24), which provides access to geranylgeranyl glycerol phosphate, an archaeal lipid. 31,32 It turned out that the method is also very useful to prepare photoswitchable phosphatidic acids. Starting from 25, (Scheme 2) a 4-butyl-azo-4 : 0-acid-1 (FAAzo-4, 30) group, the most common photo-switchable lipophilic tail, was installed with a DCC-mediated coupling reaction.…”
mentioning
confidence: 99%
“…Starting from 25, (Scheme 2) a 4-butyl-azo-4 : 0-acid-1 (FAAzo-4, 30) group, the most common photo-switchable lipophilic tail, was installed with a DCC-mediated coupling reaction. Subsequent deprotection of 35 with TMSBr provided the desired photoswitchable phosphatidic acid mimic 36, with the diazo switch intact, in 4-steps from (R)-glycidol (31). Similar switchable lipids have been prepared in more steps but a higher yield.…”
mentioning
confidence: 99%